Corporate antitrust prosecutions: prosecutorial decision making in the assessment of total monetary penalties - Braaten, Claire Nolasco (Crime, law and social change, 2024)
Our study analyzes data from the Corporate Prosecution Registry of the University of Virginia School of Law and Duke University School of Law (Garrett and Ashley, 2023). We examine a subset of corporate violators, namely prosecutions brought under the Sherman Antitrust Act’s criminal provisions. The Sherman Antitrust Act of 1890 is a federal statute that prohibits activities that restrict interstate commerce and competition in the marketplace. We utilize the framework of bounded rationality of decision making to hypothesize that prosecutors are influenced by internal and external factors that affect the total monetary penalties ultimately levied on corporate violators of the Sherman Anti-Trust Law’s criminal provisions. Specifically, our results indicate that corporate monetary penalties for antitrust corporate offenders are significantly more likely to be lower when the corporate defendant entered into disposition agreements (such as non-prosecution agreements, deferred prosecution agreements, and plea agreements) with the prosecutor and is a company incorporated and registered under U.S. laws. On the other hand, the total monetary penalties imposed on corporate defendants are more likely to be higher when the defendant is a financial institution, a public company, or a Fortune 500 company.